Monitoring Grassland Tourist Season of Inner Mongolia, China Using Remote Sensing Data - Quansheng Ge; Xi Yang; Zhi Qiao; Haolong Liu; Jun Liu (Advances in Meteorology)
Phenology-driven events, such as spring wildflower displays or fall tree colour, are generally appreciated by tourists for centuries around the world. Monitoring when tourist seasons occur using satellite data has been an area of growing research interest in recent decades. In this paper, a valid methodology for detecting the grassland tourist season using remote sensing data was presented. On average, the beginning, the best, and the end of grassland tourist season of Inner Mongolia, China, occur in late June (±30 days), early July (±30 days), and late July (±50 days), respectively. In south region, the grassland tourist season appeared relatively late. The length of the grassland tourist season is about 90 days with strong spatial trend. South areas exhibit longer tourist season.